A water-soluble oil-displacing agent with tracer properties for enhancing oil recovery1. Issue 53 (11th June 2015) - Yan, Liwei; Yin, Ting; Yu, Wenkun; Shen, Linghong; Lv, Mingqian; Ye, Zhongbin
<x xml:space="preserve">Abstract</x> A water-soluble fluorescent oil-displacing agent was prepared via copolymerization of acrylamide (AM), acrylic acid (AA) and coumarin derivatives (CO) for enhancing oil recovery.